2016
DOI: 10.3168/jds.2016-11301
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactococcus chungangensis inhibits 2,4-dinitrochlorobenzene-induced atopic-like dermatitis in NC/Nga mice

Abstract: Interest is increasing in the potentially beneficial role of probiotics in the prevention and treatment of atopic diseases. In this study, we investigated the protective effects of Lactococcus chungangensis CAU 28(T) against atopic dermatitis using murine macrophage RAW 264.7 cells, human keratinocyte HaCaT cells, human mast cell line HMC-1 cells, and a 2,4-dinitrochlorobenzene-induced atopic dermatitis model (NC/Nga mice). The results showed that L. chungangensis CAU 28(T) exhibited potent antiinflammatory ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
(66 reference statements)
1
11
1
Order By: Relevance
“…Therefore, we investigated cytokines related to Th2 in an in vivo model. Jawoongo treatment reduced the increased serum levels of IgE, IL-6, IL-10 and IL-12 induced by DNCB treatment In fact, it was reported that IL-12 was increased by DNCB [ 46 , 47 ], and this increase was suppressed by Jawoongo as expected. We also found that Jawoongo reduced DNCB-stimulated increases in eosinophil, neutrophil, monocyte, basophil, lymphocyte and WBC numbers and in IL-4, IL-13 and TNF-α mRNA expression.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, we investigated cytokines related to Th2 in an in vivo model. Jawoongo treatment reduced the increased serum levels of IgE, IL-6, IL-10 and IL-12 induced by DNCB treatment In fact, it was reported that IL-12 was increased by DNCB [ 46 , 47 ], and this increase was suppressed by Jawoongo as expected. We also found that Jawoongo reduced DNCB-stimulated increases in eosinophil, neutrophil, monocyte, basophil, lymphocyte and WBC numbers and in IL-4, IL-13 and TNF-α mRNA expression.…”
Section: Discussionsupporting
confidence: 60%
“…29 Several studies have shown that a probiotic, Lactococcus chungangensis, could improve atopic dermatitis symptoms in a COM-induced mouse model. 30 Using this model, we observed that a composite mixture of four species of probiotic bacteria and sodium butyrate mitigated atopic dermatitis symptoms due to histamine secretion. Atopic dermatitis is characterized by Th1/Th2 cells imbalance and dominant Th2 cells-mediated responses.…”
Section: Discussionmentioning
confidence: 95%
“…Probiotic bacteria can interact with the host mucosa and may beneficially modulate immune system (Choi et al . ). Previously, clinical trials involving in vivo animal models have reported that various types of LAB alleviate allergic symptoms (Kalliomaki et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Choi et al . ). Lactobacillales or lactic acid bacteria (LAB) produce lactic acid as a metabolic end‐product, and are known to prevent AD symptoms (Masuda et al .…”
Section: Introductionmentioning
confidence: 97%